Legal Consequences of Betel Marriage Settlement During the Covid-19 Pandemic - Nadia Dhea Safira Dama; Amanda Adelina Harun (Universitas Negeri Gorontalo, 2022)
This study aims to determine the legal consequences of betel marriage settlement during the Covid-19 pandemic. The type of research used is sociological juridical and this study uses a descriptive research approach and qualitative data analysis techniques. The results of this study show that the legal consequences of an unrecorded marriage can cause the marriage to be invalid in the eyes of positive Indonesian law, but according to religion and public belief that the marriage is valid as long as it meets the conditions and legal pillars of a marriage itself. As for the settlement, there are two things, namely the application for a marriage and remarriage hearing. However, the bad factor is that if the marriage partner has obtained a child, then in civil law the child does not have a nasab with the father but only has a nasab with a mother and her family.